Comorbidity Patterns of Posttraumatic Stress Disorder and Depression Symptoms: Cross-Validation in Two Postearthquake Child and Adolescent Samples - Xu, Boya; Yuan, Hao; Wu, Xinchun; Wang, Wenchao (Depression and Anxiety, 2023)
Background. Children and adolescents who have been exposed to a major natural disaster are more likely to suffer from posttraumatic stress disorder (PTSD) and depression. However, only a few studies have examined comorbidity patterns at the symptom level. Furthermore, researchers should validate their findings using multiple samples to address the psychological reproducibility challenge. Methods. The Child PTSD Symptom Scale (CPSS) and Center for Epidemiological Studies Depression Scale for Children (CES-DC) were administered to two postearthquake child and adolescent samples (Wenchuan earthquake, N=1506; Ya’an earthquake, N=720). Each sample was followed up twice. Comorbidity patterns were characterized by cross-lagged panel network analysis (CLPN), and communities were determined by bootstrap exploratory graphical analysis (bootEGA). Results. Except for having difficulty remembering important aspects of the trauma, the remaining dysphoria symptoms could be considered bridge symptoms between PTSD and depression. Most often, intrusive and avoidant symptoms clustered together, whereas dysphoria symptoms tended to cluster with depressive symptoms. The relationship between PTSD and depression was reciprocal; within PTSD, intrusive symptoms often triggered avoidance symptoms. The correlation coefficient between the two networks was 0.70, and the correlation coefficient of node centrality was 0.55. Findings. The association between dysphoria symptoms and depression was strong, and intrusive symptoms constituted the core symptoms of PTSD. Depression and PTSD were causally related, explaining the high comorbidity rates. Two sample networks had similar global characteristics but different local characteristics. The conclusions can be generalized to some extent.